Corpo e representação nos primórdios da metapsicologia freudiana (1888-1896) - Duarte, Mauro Fernando (2012)
With the aim to analyze the key concepts for the formulation of the notion of psychic and its relation to the somatic in Freud's early work, this dissertation aims to address these texts on the issue of representation, affect, and defense mechanisms, as well as their interfaces with the concept of body. It analyzes the recognition by Charcot to the importanceof psychological factors in the genesis of some types of neuroses, and as this thought seems tohave had an enormous influence on scientific direction taken by Freud since. Pillar of the psychological conception of Freud, the concept of representation supports most models of the metapsychological mental apparatus, since the Project (1895), to the Interpretation of Dreams (1900). With the redesign of many of the physicalists precepts, impressions of Charcot, as well as the vision of symptoms at the time, Freud demonstrates the texts on Aphasia and Some considerations for a comparative study between Organic and Hysterical Motor Paralysis (1893), taken by the potential language as an object of study, replacing to some extent the anatomy for understanding both the hysteria and the neuroses in general. The development of this focus is seen in the work proposed in the Project (1895), in which we see the importance of helplessness and the adult role in the formation of mnemic traits and appearance of the device: prototypical records. Start from the analysis of the influences in the early works of Freud, especially in the removal of the organic explanation for the neurotic phenomena. The distinction between affect and representation, especially with the concept of defense, is studied with the text neuropsychoses of defense (1894), marked thedevelopment of this theory. We organize the formulation of a Freudian conception of the nature of language and the concept of capital to support the defense argument in favor of the hypothesis of acquired causes in the etiology of the neuroses and the constitution of the psychic apparatus. Fundamental to the construction of the theory of the psychic apparatus, the text of the Project (1895) demonstrates the potential acquired by the language from the text of Aphasia (1891), presented in deepening the economic issue of representation. The fundamental operator of the construction of Freudian thought, the representation theory has great potential for the analysis of the contents metapsychological. We analyze the three fundamental concepts in the enrollment of experience in the psychic apparatus, in their infancy in the 1890s, but that will culminate in the topic concepts as unconscious, pulsion and repression, all derived from the energy-representational Freudian approach to. With the resumption of these concepts and their links to understand the psychic apparatus, there is a core set of hypotheses to explain psychopathological processes, the formation of the psychic apparatus and its interfaces with the somatic processes derived from an unconscious system of ideas (representations).